MODERN STORYTELLING AND ANCIENT MYTHS: FOSTERING EMPATHY AND ETHICS IN INDIAN CHILDREN’S NARRATIVES - Mishra, Subrato; Singh, Krishna Murari (International Journal of Research -GRANTHAALAYAH, 2025)
Mythological stories have always held a powerful place in shaping the moral and emotional foundations of a society. In the Indian context, timeless epics like the Mahabharata and Ramayana, along with the Puranas and Jataka Tales, are not just religious or historical texts they are rich sources of ethical guidance and cultural wisdom. These stories have been passed down through generations, offering lessons in courage, compassion, truth, and justice. In today’s complex world, retelling these ancient tales for children has become a meaningful way to nurture emotional intelligence and moral values from a young age. Modern adaptations such as Gita for Children by Roopa Pai, Ramayana for Children by Arshia Sattar, and Mahabharata for Children by Sudha Gupta reimagine these classic narratives in simple, engaging language, tailored to the understanding of young readers. Gupta’s version, for example, presents the vast epic in a child-friendly style, complete with vivid illustrations and essential episodes that capture the heart of the story. These books introduce young minds to traditional heroes and dilemmas while gently guiding them through key lessons on empathy, resilience, and integrity. By weaving mythological wisdom into accessible stories, these retellings bridge the gap between past and present. This paper explores how such narratives contribute to children’s emotional and moral development, fostering empathy and ethical awareness in a rapidly changing world.